Assessing ERP Adoption Determinants in Oil Palm Plantations Using UTAUT2 and SEM Evidence from PT Menthobi Makmur Lestari - Bimantoro Suryo Budi Sudibyo; Evi Triandini; Dadang Hermawan (Applied Information System and Management (AISM), 2026)
The palm oil plantation industry in Indonesia still faces challenges in efficiency, resource management, and operational sustainability. To overcome these challenges, Enterprise Resource Planning (ERP) systems offer integrated solutions. However, their adoption is often hindered by organizational and individual barriers. This study investigates the factors influencing ERP adoption at PT. Menthobi Makmur Lestari is using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) framework. Data were collected from 88 respondents, including managers and staff actively engaged with ERP systems, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings reveal that price value, facilitating conditions, and performance expectancy significantly and positively affect behavioral intention, which in turn drives actual system usage. Moderation analysis of age, gender, and Experience showed minimal influence, indicating that demographic characteristics play a limited role in shaping ERP adoption behavior. Instead, organizational support, infrastructure availability, and perceived economic benefits emerged as the dominant enablers of ERP adoption. The findings highlight the critical role of management strategies, training, and system alignment with employee tasks in ensuring successful ERP implementation. The study concludes that ERP adoption in palm oil companies is more strongly determined by organizational readiness than by individual differences.